Advertisement Remove all ads

Let F, G: R → R Be Defined, Respectively By F(X) = X + 1, G(X) = 2x – 3. Find F + G, F – G And `F/G` - Mathematics

Sum

Let fgR → R be defined, respectively by f(x) = + 1, g(x) = 2x – 3. Find f + gf – g and `f/g`

Advertisement Remove all ads

Solution

fgR → is defined as f(x) = + 1, g(x) = 2x – 3

(f + g) (x) = f(x) + g(x) = (x + 1) + (2x – 3) = 3x – 2

∴(f + g) (x) = 3x – 2

(f – g) (x) = f(x) – g(x) = (x + 1) – (2x – 3) = x + 1 – 2x + 3 = – x + 4

∴ (f – g) (x) = –x + 4

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 11 Mathematics Textbook
Chapter 2 Relations and Functions
Exercise 2.4 | Q 7 | Page 46
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×